2009
DOI: 10.1093/annonc/mdn640
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of full-dose gemcitabine and regional arterial infusion of nafamostat mesilate for advanced pancreatic cancer

Abstract: This phase I study was carried out safely. This combination chemotherapy showed beneficial improvement in health-related quality of life. The recommended phase II dose of nafamostat mesilate in combination with full-dose gemcitabine is 4.8 mg/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Combination chemotherapy using nafamostat mesilate and oxaliplatin induces synergistic cytotoxicity in pancreatic cancer [35]. Importantly, the median survival time of patients treated with gemcitabine plus intra-arterial nafamostat mesilate was approximately two months longer than that with the gemcitabine alone without adverse effects as demonstrated in a phase Ι study of unresectable pancreatic cancer [36]. We therefore conceptualized that both de novo and acquired resistance to therapy could be attenuated using combination therapy based on sound rationale and hypothesized that nafamostat mesilate may be a novel chemosensitizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Combination chemotherapy using nafamostat mesilate and oxaliplatin induces synergistic cytotoxicity in pancreatic cancer [35]. Importantly, the median survival time of patients treated with gemcitabine plus intra-arterial nafamostat mesilate was approximately two months longer than that with the gemcitabine alone without adverse effects as demonstrated in a phase Ι study of unresectable pancreatic cancer [36]. We therefore conceptualized that both de novo and acquired resistance to therapy could be attenuated using combination therapy based on sound rationale and hypothesized that nafamostat mesilate may be a novel chemosensitizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…We applied nafamostat mesilate a NF-κB inhibitor in our phase I and phase II studies. As the concentration of nafamostat mesilate under conditions of continuous intravenous infusion was insufficient to inhibit NF-κB activation, regional arterial infusion using a port-catheter system was selected [56]. Although the development of novel drugs for biliary-pancreatic cancer is needed, physicians currently have no choice but to use existing agents.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the median survival time achieved with the combination chemotherapy in the patients with gemcitabine-resistant pancreatic cancer was 161 days (95 % confidence interval 109-223 days), and the 1-year survival rate was 19 % [55]. Chemotherapy with nafamostat mesilate and gemcitabine was administered for locally advanced or metastatic pancreatic cancer in a phase I (n = 12) and phase II study (n = 35) [56,57]. The median survival time was 10 months (95 % confidence interval 9.3-13.5 months), with a 1-year survival rate of 40 % [57], while the response and disease control rates were 17.1 and 88.6 %, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that nafamostat mesilate inhibits NF-κB activation by suppressing IκB· phosphorylation and induces caspase-8 mediated apoptosis of pancreatic cancer cells (16). Also, high efficacy of nafamostat mesilate combined with gemcitabine for pancreatic cancer has been demonstrated in animal experiments (17) that applied to clinical trials (18). Nafamostat mesilate, which is a serine-protease inhibitor (19,20), is widely used for treatment of pancreatitis (21), disseminated intravascular coagulation (22), and anticoagulation in hemodialysis (23) in Japan, and has only minimal adverse effects such as hyperkalemia or hyponatremia (24)(25)(26).…”
Section: Introductionmentioning
confidence: 98%